Effect of phase coexistence at morphotropic phase boundary on the properties of Pb(ZrxTi1-x)O3 ceramics - Mishra S.K.; Pandey D.; Singh A.P. (My University, 2025)
The temperature variation of planar electromechanical coupling coefficient (kp) in Pb(ZrxTi1-x)O3(PZT) ceramics near the morphotropic phase boundary (MPB) compositions has been correlated with structural changes to show that the maximum electromechanical response at a given composition (x) is a function of temperature (T) and occurs in the tetragonal phase field just outside the two-phase MPB region in the (x,T) plane. This clearly disproves the hypothesis that the coexistence of rhombohedral and tetragonal phases at MPB is responsible for the enhancement of the electromechanical response. In fact, coexistence of the rhombohedral phase with the tetragonal phase is shown to lead to the lowering of the electromechanical response. © 1996 American Institute of Physics.